Polyvinylidene fluoride cladded calcite tablet for phosphate removal and reclamation from aqueous solution. Issue 6 (December 2019) - Wang, Zhenxing; Zhang, Chenling
Highlights: A PVDF cladded calcite tablet was synthesized for phosphate precipitation. Phosphate could be reclaimed as hydroxyapatite and brushite. The phosphate reclamation capacity achieved 7.66 mg g −1 at pH 4–9. The as-prepared tablet exhibited desirable reusability. Abstract: We report a core-shell tablet by encapsuling calcite in polyvinylidene fluoride (PVDF) capsules. The as-prepared material was used for the phosphate removal and reclamation from phosphate-containing wastewater. The PVDF shell exhibited desirable performance in the formation of the Ca 2+ supersaturation around the surface of the as-prepared material. The calcium-phosphate precipitates could be easily collected in the form of hydroxyapatite and brushite without impurities. The phosphate reclamation capacity achieved 7.66 mg g −1 . The equilibrium could be attained within 2 h. The best performance could be attained when initial solution pH ranged in 4–9, whereas extreme acidic/alkalic pH exhibited negative effect. In addition, the as-prepared material exhibited desirable reusability, and the phosphate reclamation capacity could be effectively recovered by calcination at 650 °C. Findings from this study proposed a promising pathway to remove and reclaim phosphate simultaneously from aqueous solution.